(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The issue of corporate Social responsibility (CSR) has become a movement in India. This article traces the Evolution of the concept of Corporate Social Responsibility in India. Understanding and examining the historical context is very important for understanding CSR practices of Indian businesses. The article traces history of CSR practices during ancient and medieval period. It also traces the evolution of modern CSR thought in the western literature and practices. Finally, it presents and analyzes the current legally mandated CSR system in India by critically examining its different components and their implication on Indian businesses and society.